PROSES PENENTUAN HARGA DI TEMPAT PELELANGAN IKAN (TPI) KECAMATAN KOTAAGUNG KABUPATEN TANGGAMUS - Aris Munandar Aris (Jurnal Kompetitif Bisnis, 2020)
This study aims to determine the method of pricing in business processes at the the fish auction place (TPI), Kotaagung district, Tanggamus regency. This type of research used in this study is a type of descriptive research with a qualitative approach. . Data analysis in this study uses the stages of data reduction, data presentation, drawing conclusions. Data collection techniques used were observations carried out at TPI Kotaagung, interviews with Kotaagung fishermen, TPI Kotaagung Officers, fish packing and documentation. The results showed the determination of the price for each type of fish is different, the price is determined by the auctioneer because in this auction process, the auctioneer has collected a certain minimum price. Determination of the price is adjusted to the requirements of fish / quality of fish and volume of fish, in an open bargaining process, the price of fish is above the highest price and is determined as the auction winner